Analysis of transcriptional response to heat stress in Rhazya stricta. Issue 1 (December 2016) - Obaid, Abdullah; Sabir, Jamal; Atef, Ahmed; Liu, Xuan; Edris, Sherif; El-Domyati, Fotouh; Mutwakil, Mohammed; Gadalla, Nour; Hajrah, Nahid; Al-Kordy, Magdy; Hall, Neil; Bahieldin, Ahmed; et al.
Abstract Background Climate change is predicted to be a serious threat to agriculture due to the need for crops to be able to tolerate increased heat stress. Desert plants have already adapted to high levels of heat stress so they make excellent systems for identifying genes involved in thermotolerance.Rhazya stricta is an evergreen shrub that is native to extremely hot regions across Western and South Asia, making it an excellent system for examining plant responses to heat stress. Transcriptomes of apical and mature leaves ofR. stricta were analyzed at different temperatures during several time points of the day to detect heat response mechanisms that might confer thermotolerance and protection of the plant photosynthetic apparatus. Results Biological pathways that were crosstalking during the day involved the biosynthesis of several heat stress-related compounds, including soluble sugars, polyols, secondary metabolites, phenolics and methionine. Highly downregulated leaf transcripts at the hottest time of the day (40–42.4 °C) included genes encoding cyclin, cytochrome p450/secologanin synthase and U-box containing proteins, while upregulated, abundant transcripts included genes encoding heat shock proteins (HSPs), chaperones, UDP-glycosyltransferase, aquaporins and protein transparent testa 12. The upregulation of transcripts encoding HSPs, chaperones and UDP-glucosyltransferase and downregulation of transcripts encoding U-box containing proteins likely contributed to thermotolerance inR. stricta leaf by correcting protein folding and preventing protein degradation. Transcription factors that may regulate expression of genes encoding HSPs and chaperones under heat stress included HSFA2 to 4, AP2-EREBP and WRKY27. Conclusion This study contributed new insights into the regulatory mechanisms of thermotolerance in the wild plant speciesR. stricta, an arid land, perennial evergreen shrub common in the Arabian Peninsula and Indian subcontinent. Enzymes from several pathways are interacting in the biosynthesis of soluble sugars, polyols, secondary metabolites, phenolics and methionine and are the primary contributors to thermotolerance in this species.